OPTIMALISASI TA'ZIR SEBAGAI STRATEGI PEDAGOGIS DALAM PENINGKATAN DISIPLIN SANTRI DI PONDOK PESANTREN NURUL JADID PAITON - Yusrowiyah; Mistria Harmonis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student discipline in Islamic boarding schools remains a significant issue because the implementation of ta'zir (religious guidance) as a development tool has not been fully effective in reducing recurrent violations. This study aims to analyze the optimization of ta'zir as a pedagogical strategy to improve student discipline at the Nurul Jadid Paiton Islamic Boarding School. This study used a qualitative approach with field research techniques using observation, interviews, and case study documentation. The results indicate that ta'zir plays a crucial role in fostering students' awareness of discipline through a point system, clarification of sanctions, and the implementation of additional educational and social rules. However, its effectiveness is not optimal due to the persistence of recurrent violations, influenced by students' low understanding, a lack of variety in sanctions, and inconsistent supervision. The implementation of new policies, such as the addition of social sanctions, can foster a sense of shame and responsibility, thus encouraging changes in student behavior toward greater discipline. Thus, ta'zir functions not only as punishment but also as a means of ongoing character education.